2016
DOI: 10.1007/s11032-016-0569-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of α-gliadin expressed genes in genetically contrasted spelt (Triticum aestivum ssp. spelta) accessions and comparison with bread wheat (T. aestivum ssp. aestivum) and related diploid Triticum and Aegilops species

Abstract: The gluten proteins of cereals such as bread wheat (Triticum aestivum ssp. aestivum) and spelt (T. aestivum ssp. spelta) are responsible for celiac disease (CD). The α-gliadins constitute the most immunogenic class of gluten proteins as they include four main T-cell stimulatory epitopes that affect CD patients. Spelt has been less studied than bread wheat and could constitute a source of valuable diversity. The objective of this work was to study the genetic diversity of spelt α-gliadin transcripts and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 65 publications
8
29
0
1
Order By: Relevance
“…Each of these four epitopes can be displayed in its canonical form, which is toxic, but some amino acid substitutions or deletions can reduce or suppress antigenic properties, according to the allelic variant [ 27 ]. Interestingly, the epitope variants highlighted in bread wheat α-gliadin sequences by Mitea et al [ 27 ] were similar to those found in spelt accessions [ 16 ].The multigenic character of the α-gliadin family results in a very high allelic variability and leads, among other things, to high variations in the immunogenic content from one α-gliadin sequence to another. The exploitation of this variability to develop safe spelt or wheat cultivars will probably require the combination of classical breeding and molecular technologies [ 12 ], and tools to infer the presence of sequences coding for toxic epitopes are needed.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Each of these four epitopes can be displayed in its canonical form, which is toxic, but some amino acid substitutions or deletions can reduce or suppress antigenic properties, according to the allelic variant [ 27 ]. Interestingly, the epitope variants highlighted in bread wheat α-gliadin sequences by Mitea et al [ 27 ] were similar to those found in spelt accessions [ 16 ].The multigenic character of the α-gliadin family results in a very high allelic variability and leads, among other things, to high variations in the immunogenic content from one α-gliadin sequence to another. The exploitation of this variability to develop safe spelt or wheat cultivars will probably require the combination of classical breeding and molecular technologies [ 12 ], and tools to infer the presence of sequences coding for toxic epitopes are needed.…”
Section: Introductionsupporting
confidence: 71%
“…It is particularly interesting because of the high genetic diversity held in spelt germplasm collections [ 13 – 15 ]. Moreover, genetic variations in their immunogenic potential, their bread-making qualities and their content in proteins, lipids, micronutrients and fibers have been pointed out [ 13 , 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these traditional foods in the diet, the diet may cause inconvenience for the patients. That is why selectionists do research and improve existing varieties in order to remove the corresponding allergens for spelt wheat to become valuable raw material [16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Ancient tetraploid wheat species have also been analyzed in this manner, and studies have shown that ancient durum wheat species found in Italy are not celiac safe [7]. In recent studies by Dubois et al [8,9] and Escarnot et al [10], the celiac immunogenicity of spelt and hexaploid wheat was investigated where they found that there is large variation among different spelt accessions regarding their celiac reactivity. In these studies, various methods such as ELISA were used for the quantitative analysis of celiac epitopes.…”
Section: Introductionmentioning
confidence: 99%